Methods and Materials for Non-Medical Students to Enhance Medical Literature Reading - Zheng, Jie; Xiong, Lingsong; Luo, Ruifeng (International Journal of Membrane Science and Technology, 2023)
Medical English (ME) is of paramount importance both in theory and practice, and the need for professionals with high proficiency in ME has increased due to the COVID-19 pandemic. The EMP (English for Medical Purposes) teaching methods and materials for medical students have been widely discussed, while the learning process of non-medical students is ignored. Non-medical students have various difficulties in reading medical English literature because of their different proficiency of general English and absence of medical knowledge. Considering ME’s utilitarian nature and unique lexicon and syntax, this paper discusses four main approaches to help non-medical students to enhance medical literature reading, including Johns and Davies’ TAVI approach, Divasson’s reading strategies for different types of medical prose, Pavel’s focus on grammar and lexicon, and Hamid Rushwan’s aiding tool of machine translation. Non-medical students are recommended to focus more on the practical information involved in literature than the lexical and syntactic analysis, though it is still meaningful to analyze words and sentences to get used to the common usages of lexicon and syntax. Machine translation also aids reading comprehension for non-medical students. Textbooks, journals, and multimedia vehicles are recommended for non-medical students to acquire medical English and improve their reading proficiency.